PERANCANGAN MAIL SERVER ZIMBRA MENGGUNAKAN TEKNOLOGI VIRTUALISASI STUDI KASUS : SMK PANCAKARYA KOTA TANGERANG - Heru Prasetiawan (LPPM STMIK Pringsewu, 2016)
The development of information technology is growing rapidly spur the emergence of new technologies are constantly evolving. The development of technologies that generate more reliable, efficient, economical, and powerful than previous technology. Electronic mail (email) is a form of communication and correspondence electronically through a computer system and transmitted to another computer that is intended to traverse the computer network. The existence of mail server is needed to support the communication needs via email. Zimbra Mail Server is implemented using virtualization technology with the operating system Proxmox which is a Linux distribution based on Debian and to guestnya operating system SLES (Suse Linux Enterprise Server). This research was conducted at the agency already has a previous computer networking facilities, so that the research was conducted to complement the needs of the mail server at the institution. The result achieved is a mail application server using virtualization technology that has the facilities and the web-based mail client applications, antivirus and antispam.